Choosing between intensive and less intensive front-line treatment approaches for older patients with newly diagnosed acute myeloid leukaemia. Issue 7 (July 2022) - Short, Nicholas J; Kantarjian, Hagop
Summary: The outcomes of older patients with acute myeloid leukaemia are inferior to their younger counterparts, because, in part, of a more aggressive disease biology and poorer tolerance of cytotoxic chemotherapy. Although intensive chemotherapy was historically considered the only effective treatment for these patients, many older patients are not suitable for intensive chemotherapy owing to comorbidities or general frailty. Determination of patient fitness for intensive chemotherapy is imperfect, and even older patients who appear to be suitable (also known as fit) for intensive chemotherapy can have high rates of morbidity and early and late mortality with this approach. Fortunately, the outcomes of older or unfit patients with acute myeloid leukaemia have substantially improved with the use of a hypomethylating agent plus venetoclax in the front-line setting. Although the formal approval of this combination is limited to patients aged 75 years or older, or those with a clinically significant comorbidity, the high response rates and survival improvement in these patients have led many practitioners to consider this low-intensity regimen in older patients without significant comorbidities and even in younger patients with high-risk disease features for whom the expected outcomes with intensive chemotherapy are poor. Modifications to the hypomethylating agent plus venetoclax backbone might further improve the outlook for these patients, particularly in some acute myeloid leukaemia subsets with a targetable mutation. In this Viewpoint, we review the retrospective and prospective data supporting both intensive chemotherapy and low-intensity venetoclax-based approaches in older patients with acute myeloid leukaemia. We also discuss our own approach to the management of older or unfit patients with acute myeloid leukaemia, including how cytomolecular features have a role in establishing the optimal front-line therapy.